CALLIGRAPHY ART AS A MEDIUM OF DA'WAH IN THE DEVELOPMENT OF ISLAM - Ahsani Madina (Yayasan Haiah Nusratul Islam, 2024)
Islamic boarding schools are known by the public because many of the works of students are introduced through culture and religion so that these works are known to the outside community. At Islamic boarding school students are also taught to study religion and deepen efforts to create a generation whose character is shaped in accordance with Islamic law. So it is no longer surprising if alumni of Islamic boarding schools are found who have good scientific character. If a work of calligraphy is found in a shop, the first thing that comes to mind is that the work is one of the works of Islamic boarding school children. So that it attracts the attention of parents to enter their children into Islamic boarding schools because of the works made by these students. Developments that can be seen at this time are the many impacts of the influence of calligraphy in Islamic boarding schools and outside Islamic boarding schools. The impact with the existence of calligraphy has had an influence on the development of Islam. The purpose of writing this article is to find out how the role of Islamic boarding schools is in developing the art of calligraphy as a medium for preaching the development of Islam. In this study the authors used descriptive qualitative methods through a literature study approach, taking reference materials from journals, books, articles, and others, as mandatory material in this research.